2003
DOI: 10.1046/j.1365-2249.2003.02145.x
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of plasma nerve-growth factor detection is associated with death of memory B lymphocytes in HIV-1 infection

Abstract: SUMMARYNerve growth factor (NGF) regulates B cell activation and differentiation and is an autocrine survival factor for memory B lymphocytes. We have reported recently that the number of memory B cells is reduced during HIV-1 infection. In this study we evaluated whether alteration in the NGF supply was involved in memory B cell loss in HIV-1-infected subjects. High rate of cell death in vitro was observed in memory B cells from HIV-1-infected individuals compared to uninfected donors (26·2 ± 2·5% versus 7·9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 38 publications
(51 reference statements)
2
28
0
Order By: Relevance
“…This approach required that HIV-specific B cells not only survive the in vitro culture period but also respond to the stimulation by undergoing terminal differentiation. There is good reason to believe that memory B cells of HIV-infected viremic individuals may be defective in these ex vivo processes, given their increased propensity to undergo apoptosis compared with memory B cells from HIV-uninfected and HIV-aviremic individuals (49)(50)(51)(52). The recent development of trimeric HIV envelope probes that can measure directly HIV-specific B cells (15), without in vitro manipulation, represents a major advancement for studying humoral immunity against the virus.…”
Section: Discussionmentioning
confidence: 99%
“…This approach required that HIV-specific B cells not only survive the in vitro culture period but also respond to the stimulation by undergoing terminal differentiation. There is good reason to believe that memory B cells of HIV-infected viremic individuals may be defective in these ex vivo processes, given their increased propensity to undergo apoptosis compared with memory B cells from HIV-uninfected and HIV-aviremic individuals (49)(50)(51)(52). The recent development of trimeric HIV envelope probes that can measure directly HIV-specific B cells (15), without in vitro manipulation, represents a major advancement for studying humoral immunity against the virus.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that memory B lymphocytes from HIV-1-infected subjects undergo spontaneous apoptosis in vitro, 6,30 suggesting that this alteration may account for the dysfunctions in humoral immunity. Many studies have indicated a defect in the humoral immunity toward several antigens 9,11,26,27 and such a defect may be due to the deletion of antigen-specific CD4 ϩ T cells or to the loss of memory B cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that the reduction of circulating memory B cells observed in HIV-1 infection is associated with a significant increase of spontaneous cell death in vitro of memory B lymphocytes. 6,30 In the populations described here we confirm that memory B lymphocytes are reduced in HIV-1 infection as compared with uninfected controls (20% [range, 6.8%-43%] vs 34.3%, [range, 21.1%-60.7%]; P Ͻ .001) and that these cells exhibit higher spontaneous apoptosis as compared with the cells from healthy subjects (26.2% Ϯ 2.5% vs 7.9% Ϯ 1.4%; P Ͻ .001). Moreover, regression analysis performed on treatment-naive patients showed that the percentage of memory B cells inversely correlates with the HIV-1 plasma viral load (r ϭ 0.45, P ϭ .02).…”
Section: Loss Of Antigen-specific Humoral Immunity In Hiv-1 Infectionmentioning
confidence: 99%
See 2 more Smart Citations